Efektivitas Peran Keluarga dalam Membentuk Tumbuh Kembang Agama - Asmaya, Enung (Fakultas Dakwah IAIN Purwokerto, 2017)
Religion is the choice of human life. Man can accept or reject religion is influenced by their knowledge, attitude and experience, or known as personal and social aspects. These two aspects influence each other in determining human behavior. Human are individuals who are integrated and live with both aspects. Man will be lucky if able managing both aspects on the path of truth. But man will lose if otherwise. Based on the theory of behaviorism aspects social as family becomes the determinant in the verdict of religious behavior someone. Because the family becomes the closest place in one’s life.Many norms, the rule of leadership in the family which becomes the frame of references of a person in behaving. Therefore in a religious, healthy, prosperous and harmonious family the positive influence of one’s religious adherence. Beragama adalah pilihan hidup manusia. Manusia dapat menerima atau menolak agama dipengaruhi pengetahuan, sikap, dan pengalaman yang dimiliki yang biasa disebut aspek personal dan sosial. Kedua aspek tersebut saling memengaruhi jiwa dalam menentukan perilaku manusia. Manusia adalah individu yang terintegrasi dari kedua aspek tersebut dan manusia hidup dengan kedua aspek tersebut. Manusia akan beruntung jika mampu mengelola kedua aspek tersebut pada jalan kebenaran. Namun manusia akan merugi jika sebaliknya. Berdasarkan teori behaviorisme, aspek-aspek sosial seperti keluarga menjadi penentu dalam putusan perilaku keagamaan seseorang. Keluarga menjadi tempat yang paling dekat dalam kehidupan seseorang. Banyak norma, aturan kepemimpinan dalam keluarga yang menjadi frame of references seseorang dalam berperilaku. Keluarga yang agamis, sehat, sejahtera, dan harmonis memberikan pengaruh positif kepatuhan beragama seseorang.